Is drug release necessary for antimicrobial activity of siderophore-drug conjugates? Syntheses and biological studies of the naturally occurring salmycin “Trojan Horse” antibiotics and synthetic desferridanoxamine-antibiotic conjugates - Wencewicz, Timothy A. (2009)
The recent rise in drug resistance found amongst community acquired infections has sparked renewed interest in developing antimicrobial agents that target resistant organisms and limit the natural selection of immune variants. Recent discoveries have shown that iron uptake systems in bacteria and fungi are suitable targets for developing such therapeutic agents. The use of siderophore-drug conjugates as “Trojan Horse” drug delivery agents has attracted particular interest in this area. This review will discuss efforts in our research group to study the salmycin class of “Trojan Horse” antibiotics. Inspired by the natural design of the salmycins, a series of desferridanoxamine-antibiotic conjugates were synthesized and tested in microbial growth inhibition assays. The results of these studies will be related to understanding the role of drug release in siderophore-mediated drug delivery with implications for future siderophore-drug conjugate design.